Effect Of Viral Marketing And Brand Awareness On Purchase Intention With Customer Trust As A Mediation Variable in TikTok Shop User (The Manager Review, 2024)
Work ethic, organizational commitment, and competence represent critical dimensions of employee performance. A robust work ethic enhances productivity and discipline, while organizational commitment promotes employee loyalty and motivation. Competence, encompassing both technical knowledge and skills, plays an essential role in overall organizational performance. The interplay among these three factors can substantially impede the achievement of organizational objectives. This study aims to investigate the influence of work ethic, organizational commitment, and employee competence on employee performance at PT Dirgantara Indonesia. As a strategic entity within the aerospace industry, PT Dirgantara Indonesia confronts significant challenges in maintaining and enhancing employee performance, which is vital for organizational success. The research employed a quantitative approach with an explanatory design. Data were collected from 307 employees at PT Dirgantara Indonesia through the use of questionnaires. The analytical techniques utilized include multiple linear regression, t-tests for partial influence, and F-tests for simultaneous influence, with analysis conducted using SPSS version 23. The research results reveal that work ethic has a positive but not statistically significant effect on employee performance. On the other hand, organizational commitment shows a positive and significant influence on employee performance. Furthermore, employee competency turns out to have a positive and significant influence on employee performance. Then, after joint testing of the variables, work ethic, organizational commitment and employee competency made a significant contribution to employee performance at PT Dirgantara Indonesia.